Endovascular treatment of bifurcation intracranial aneurysms with the WEB SL/SLS: 6-month clinical and angiographic results. Issue 4 (August 2015) - Bozzetto Ambrosi, Patricia; Gory, Benjamin; Sivan-Hoffmann, Rotem; Riva, Roberto; Signorelli, Francesco; Labeyrie, Paul-Emile; Eldesouky, Islam; Sadeh-Gonike, Udi; Armoiry, Xavier; Turjman, Francis
Background: The WEB device is a recent intrasaccular flow disruption technique developed for the treatment of wide-necked intracranial aneurysms. To date, a single report on the WEB Single-Layer (SL) treatment of intracranial aneurysms has been published with 1-months' safety results. The aim of this study is to report our experience and 6-month clinical and angiographic follow-up of endovascular treatment of wide-neck aneurysm with the WEB SL. Methods: Ten patients with 10 unruptured wide-necked aneurysms were prospectively enrolled in this study. Feasibility, intraoperative and postoperative complications, and outcomes were recorded. Immediate and 6-month clinical and angiographic results were evaluated. Results: Failure of WEB SL placement occurred in two cases. Eight aneurysms were successfully treated using one WEB SL without additional treatment. Three middle cerebral artery, four anterior communicating artery, and one basilar artery aneurysms were treated. Average dome width was 7.5 mm (range 5.4–10.7 mm), and average neck size was 4.9 mm (range 2.6–6.5 mm). No periprocedural complication was observed, and morbi-mortality at discharge and 6 months was 0.0%. Angiographic follow-up at 6 months demonstrated complete aneurysm occlusion in 2/8 aneurysms, neck remnant in 5/8 aneurysms, and aneurysm remnant in 1/8 aneurysm. Conclusions: From this preliminary study, treatment of bifurcation intracranial aneurysms using WEB SL is feasible. WEB SL treatment seems safe at 6 months; however, the rate of neck remnants is not negligible due to compression of the WEB SL. Further technical improvements may be needed in order to ameliorate the occlusion in the WEB SL treatment.